2010
DOI: 10.5713/ajas.2010.90491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Arachidonic Acid (20:4n-6) Levels on Growth Performance and Fatty Acid Composition of Juvenile Eel, Anguilla japonica

Abstract: This study was conducted to evaluate the effects of dietary arachidonic acid (AA, 20:4n-6) levels on growth performance and body composition in juvenile eel, Anguilla japonica. Six semi-purified experimental diets were formulated to be isonitrogenous and iso-caloric containing 55.0% crude protein and 15% crude lipid (18.3 kJ of available energy g -1 ). Six different levels of AA were added to the basal diet, with 0, 0.2, 0.4, 0.6, 0.8 or 1.2% on a dry matter (DM) basis, respectively (AA 0.07 , AA 0.22 , AA 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…A growthpromoting activity of dietary ARA in different fish species, particularly during juvenile stages, has been reported. For example, in juvenile eel (Anguilla japonica) dietary ARA inclusion has been shown to be essential for normal growth (Bae et al, 2010), and similarly the importance of dietary ARA inclusion in larvae of sea bass (Dicentrarchus labrax) and sea bream (Sparus aurata) has been reported (Atalah et al, 2011;Bessonart et al, 1999). In juvenile Japanese seabass (Lateolabrax japonicus) and juvenile Synechogobius hasta it has been shown that dietary ARA significantly enhanced growth and protein content of the whole body and the liver (Luo et al, 2012;Xu et al, 2010).…”
mentioning
confidence: 97%
“…A growthpromoting activity of dietary ARA in different fish species, particularly during juvenile stages, has been reported. For example, in juvenile eel (Anguilla japonica) dietary ARA inclusion has been shown to be essential for normal growth (Bae et al, 2010), and similarly the importance of dietary ARA inclusion in larvae of sea bass (Dicentrarchus labrax) and sea bream (Sparus aurata) has been reported (Atalah et al, 2011;Bessonart et al, 1999). In juvenile Japanese seabass (Lateolabrax japonicus) and juvenile Synechogobius hasta it has been shown that dietary ARA significantly enhanced growth and protein content of the whole body and the liver (Luo et al, 2012;Xu et al, 2010).…”
mentioning
confidence: 97%
“…Based on data from the FAO (2016), the global market demand for eel was 285,342 tons/year with a price range between Rp 150,000/kg-Rp 255.000/kg. This high demand of eel due to its advantages including the flesh is soft, tastes good, and contains important nutrients like DHA, EPA, and vitamin A (Bae et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated the importance of ARA in fish metabolism, and it is known to be the main fatty acid precursor of eicosanoids in fish (Bell and Dick 1990;Bell et al 1994Bell et al , 2016Atalah et al 2010;Yuan et al 2015). In addition, research has been conducted on dietary ARA in several fish species, and these studies have confirmed that elevated ARA can improve growth and survival (Bessonart et al 1999;Bell and Sargent 2003;Bae et al 2010) as well as resistance to handling stress (Koven et al 2001). In addition to the selective incorporation of ARA in COM Walleye juveniles, we also observed a higher selective incorporation of DHA in COM fish compared to EXP fish.…”
Section: Fatty Acid and Nutritional Ratiomentioning
confidence: 95%